A critical evaluation of labour migrancy and practices of remittances: the case of Ghanaian workers in the informal economy in Johannesburg - Dodoo, Gifty Naa Densuah (My University, 2009)
ABSTRACT The research was inspired by further studies conducted on remittances indicating that; voluntary migrants worldwide remit generously to their families back home (Adams Jnr. 2006; Mazzucato et al., 2004a; Pendleton et al., 2006; Shady, 2004; Stark, 1991) with little attention paid to Ghanaians involved in labour migrancy in South Africa. This report explored remittance practices by Ghanaian labour migrants involved in the informal economy in Johannesburg and also investigated factors that motivated migrants from Ghana to send money and/or goods back home. The study objectives included identifying channels used to remit, frequency of remittance, different forms of remittances and also investigated the living conditions and nature of work of migrants. Finally, it established why these migrants chose to come to South Africa. A snowball sample was employed to gather data from 20 Ghanaian migrants involved in labour migrancy in the informal economy in Johannesburg. These respondents work at these various places: Parktown, Berea, Yeoville, and Braamfontein and engaged in such work as hairdressing, waiting, tailoring/clothing designing, hairdressing, Internet café operating, welding, barbering, Carpentry, shoe and bag repairing. It therefore appeared that most of these respondents got employed through social networks. Even though it was not the focus of the study, of the total population, 5 females were interviewed to explore their remittance practices compared to their male counterparts. Semi-structured interviews were used to address the research objectives. Though the research revealed two motivating factors namely; economic and social that influenced respondents to sent money to family members, economic factor emerged as the common factor among these migrants. Specific reasons for remitting among the migrants were also categorised as altruism, pure self-interest or “enlightened self-interest”. Further, the survey revealed two channels that were used by these migrants to remit family members back home. These were formal and informal channels. Under the formal channels were specialised money transfer institutions (Standard Bank, Rennies) and then sea freight services. The study saw that majority (75%) of the respondents (all the 5 female migrants inclusive) used the formal channel to transfer money or goods whereas a handful (25%) of the respondents reported to remit through personal contacts which falls under the informal channel. In terms of frequency of remittance, two trends were identified and these were regular and occasional. Migrants who remitted once, twice in every quarter or four months were categorised under regular remitters and among were the 5 female migrants interviewed, while occasional remitters were seen as those who sent money and goods once in 6 months or a year. All respondents reported to have remitted due to economic downturn in Ghana. The data collected highlighted all respondents came to South Africa for jobs that would offer better opportunities because of an impression they (migrants) had on South Africa’s economy.